An anonymous electronic voting scheme for multiple elections using a variant of the ElGamal digital signature. (16th April 2021) - Zahhafi, Leila; Khadir, Omar
In this paper we present an electronic voting protocol valid for multiple elections. The work is based on a variant of the ElGamal digital signature. Our proposed method allows to run t elections using the same parameters. We use the RSA blind signature for all transactions in the voting process. Security and complexity of the presented scheme are analysed.